Early Marriage and Household Vulnerability: Case Study in Medan Sinembah Village, Tanjung Morawa District, Deli Serdang Regency - Cholis Hamdani; Abdurrahman Abdurrahman (Edumaspul: Jurnal Pendidikan, 2024)
Marrying at an early age means getting married at an immature age. This research aims to analyze the impact of early marriage on divorce rates, and analyze the problems experienced by teenagers who marry early after deciding to divorce. The type of research used is descriptive research with a qualitative approach. This research was conducted in Medan Sinembah Village, District. Tanjung Morawa District. Deli Serdang. This research began on 17 February 2023 to 17 December 2023. The results of the research show that early marriage can increase the divorce rate because of the mental unpreparedness of teenagers who marry early in marriage, not being able to support their families because they do not have a permanent job so they often still depend on parents, whose thinking is still unstable in resolving household problems, often use emotions, infidelity, and do not have firm boundaries regarding values ​​and norms in interacting outside the home. The problems faced by teenagers who marry early after divorce include being a topic of discussion in society because they have the status of widows/widowers at a young age, difficulties in adapting to the environment because they feel embarrassed about their widow/widower status, and the breakdown of friendly relations between former families. husband and wife.